math
posted by janet .
2x squared plus 6 x plus 3 is equal to 0.....

2x^2 + 6x +3 = 0
That does not factor into terms with integers. Use the quadratic formula
x= [b +/sqrt(b^24ac)]/2a
x = [6 +/sqrt(36 24)]/4
= [6 +/sqrt12]/4
= 2.366 or 0.634 
2 x ^ 2 + 6 x + 3 = 0
Compare your equation to the standard form :
a x ^ 2 + b x + c = 0
and identify the values for a , b , c.
a = 2
b = 6
c = 3
Now evaluate the discriminant :
b ^ 2  4 a c = 6 ^ 2  4 * 2 * 3 = 36 
24 = 12
Since b ^ 2  4 ac > 0 there are two unequal real solutions:
x1 = [  b + sqrt ( b ^ 2  4 a c ) ] / 2 a
x1 = [  6 + sqrt ( 12 ) ] / 2 * 2
x1 = [  6 + sqrt ( 4 * 3 ) ] / 4
x1 = [  6 + 2 * sqrt ( 3 ) ] / 4
x1 = 2 * [  3 + sqrt ( 3 ) ] / 2 * 2
x1 = [  3 + sqrt ( 3 ) ] / 2
x1 = [ sqrt ( 3 )  3 ] / 2
x1 =  0.63 approx.
x2 = [  b  sqrt ( b ^ 2  4 a c ) ] / 2 a
x2 = [  6  sqrt ( 12 ) ] / 2 * 2
x2 = [  6  sqrt ( 4 * 3 ) ] / 4
x2 = [  6  2 * sqrt ( 3 ) ] / 4
x2 = 2 * [  3  sqrt ( 3 ) ] / 2 * 2
x2 = [  3  sqrt ( 3 ) ] / 2
x2 = [  3  sqrt ( 3 ) ] / 2
x2 =  2.37 approx.